Circulating follistatin in relation to energy metabolism. (15th September 2016) - Hansen, Jakob Schiøler; Plomgaard, Peter
Abstract: Recently, substantial evidence has emerged that the liver contributes significantly to the circulating levels of follistatin and that circulating follistatin is tightly regulated by the glucagon-to-insulin ratio. Both observations are based on investigations of healthy subjects. These novel findings challenge the present view of circulating follistatin in human physiology, being that circulating follistatin is a result of spill-over from para/autocrine actions in various tissues and cells. Follistatin as a liver-derived protein under the regulation of glucagon-to-insulin ratio suggests a relation to energy metabolism. In this narrative review, we attempt to reconcile the existing findings on circulating follistatin with the novel concept that circulating follistatin is a liver-derived molecule regulated by the glucagon-to-insulin ratio. The picture emerging is that conditions associated with elevated levels of circulating follistatin have a metabolic denominator with decreased insulin sensitivity and/or hyperglucagoneimia. Highlights: Circulating follistatin is increased in conditions associated with insulin resistance. The glucagon-to-insulin ratio has been identified to regulate circulating follistatin. The liver is a major source of the circulating follistatin in humans. This implies that circulating follistatin is related to energy metabolism. These observations elucidate why plasma follistatin is associated with insulin resistance.